How do delivery mode and parity affect pelvic organ prolapse?. (8th April 2013) - Yeniel, A. Özgür; Ergenoglu, A. Mete; Askar, Niyazi; Itil, Ismaİl Mete and Meseri, Reci
Abstract: Objective: To determine the association between mode of delivery, parity, and pelvic organ prolapse, as assessed by the pelvic organ prolapse quantification system. Design: Cross‐sectional study. Setting: Tertiary referral center, Turkey. Population: A total of 1964 women with benign gynecological disorders who presented between October 2009 and July 2011. Methods: Evaluation using the pelvic organ prolapse quantification system and questionnaire assessing previous obstetrics and medical history. Main outcome measures: Difference in pelvic organ prolapse stages between nulliparous and multiparous women, impact of parity and mode of delivery. Results: In the study population, 86.4, 7.2 and 6.4% had pelvic organ prolapse of stages 0–I, II, and III–IV, respectively, and 7.9% had significant prolapse beyond the hymen. The mean age, parity, and number of vaginal deliveries were significantly higher in the prolapse than in the non‐prolapse group. Vaginal delivery was associated with an odds ratio of 2.92 (95% confidence interval 1.19–7.17) for prolapse when compared with nulliparity. Each vaginal delivery increased the risk of prolapse (odds ratio 1.23; 95% confidence interval 1.12–1.35) after controlling for all confounding factors. Cesarean delivery had no impact on the odds for prolapse. Conclusions: Vaginal delivery was an independent risk factor for prolapse, and additional vaginal deliveries significantly increased the risk. However, cesarean delivery had no effect on the development of prolapse in this material.